2017
DOI: 10.1097/prs.0000000000003048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Acellular Dermal Matrices in Breast Reconstruction: The 50/50 Study

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 37 publications
3
29
0
1
Order By: Relevance
“…Previously, studies have suggested that AlloDerm has an increased rate of Red Breast Syndrome, however, only one case was identified in this study. 26 Capsular contracture (Grade III/IV) was seen in 3.0% of patients, which is similar to other reports in the literature, crediting ADM for being associated with low rates of capsular contracture when compared to implant-based reconstruction without ADM. 24,27 We need to outline, however, that the follow-up period, which has a wide range, precludes us from drawing definitive conclusions and possible underestimates the occurrence of capsular contracture in this patient population.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previously, studies have suggested that AlloDerm has an increased rate of Red Breast Syndrome, however, only one case was identified in this study. 26 Capsular contracture (Grade III/IV) was seen in 3.0% of patients, which is similar to other reports in the literature, crediting ADM for being associated with low rates of capsular contracture when compared to implant-based reconstruction without ADM. 24,27 We need to outline, however, that the follow-up period, which has a wide range, precludes us from drawing definitive conclusions and possible underestimates the occurrence of capsular contracture in this patient population.…”
Section: Discussionsupporting
confidence: 86%
“…Reasons for this might include the number of drains and length of time that drains were left in place, which was somewhat longer than from reports of other groups. Previously, studies have suggested that AlloDerm has an increased rate of Red Breast Syndrome, however, only one case was identified in this study . Capsular contracture (Grade III/IV) was seen in 3.0% of patients, which is similar to other reports in the literature, crediting ADM for being associated with low rates of capsular contracture when compared to implant‐based reconstruction without ADM .…”
Section: Discussionsupporting
confidence: 82%
“…This allows for compliance during prosthetic breast reconstruction, maintaining lower pole coverage and support and allowing for more aesthetic contour. 8,11 Sbitany et al published a retrospective review comparing complete submuscular placement and partial subpectoral placement with an ADM inferior sling and reported that the use of ADM allowed for a greater initial fill volume of the tissue expander with 412 mL per expander in the ADM group versus 130 mL per expander in the total submuscular group (p ¼ 0.0001) as well as approximately three less fills for the ADM group versus the total submuscular group to complete the reconstruction. 4 The study concluded that using ADM may potentially improve cosmetic outcomes by capitalizing on preserved mastectomy skin as well offering the potential for more predictable revision surgeries.…”
Section: Pocket Creation and The Use Of Acellular Dermal Matrixmentioning
confidence: 99%
“…Most importantly, initial transplantations of recellularized organs have demonstrated limited function leading to ultimate failure [ 89 91 ]. Nevertheless, it is promising to see that less complex decellularized human tissues such as skin, have been used for decades without any obvious immune rejection issues [ 92 , 93 ]. While whole organ engineering could lead to the ultimate cure for diseases such as heart and lung failure, the complex nature of tissue organization presents many challenges before this techniques is ready for therapeutic use.…”
Section: Part Ii: Microenvironmental Manipulation Of Cell Fates For Rmentioning
confidence: 99%